Melanism and color saturation of butterfly assemblages: A comparison between a tropical rainforest and a xeric white forest - Schirmer, Sofia Coradini; Gawryszewski, Felipe Malheiros; Cardoso, Márcio Zikán; Pessoa, Daniel Marques Almeida (Frontiers in Ecology and Evolution, 2023)
Traditionally, the study of butterfly coloration has helped to identify the ecological pressures involved in the evolution of animal coloration. Butterfly colors have been linked to camouflage, socio-sexual signaling, thermoregulation, parasite avoidance, and protection against desiccation and UV light. However, almost all studies that addressed this issue have focused on species that inhabit more temperate environments, leaving the species and ecological factors of tropical regions mostly understudied. Here, our purpose was to evaluate whether butterfly assemblages from two distinct Neotropical biomes (i.e., tropical rainforest and xeric white forest) differ regarding their melanism and/or color saturation. Our hypotheses were that melanism, differences in melanism between dorsal and ventral wing surfaces, and color saturation should differ between shaded/humid and open/arid tropical environments. Therefore, we quantified melanism and different spectrometric parameters (which described color saturation) from dorsal and ventral surfaces of 48 different butterfly species. Comparisons show that rainforest butterflies, when compared to white forest butterflies, have ventral wing surfaces which are, in general, more saturated in color. In addition, rainforest butterflies also have ventral and dorsal wing surfaces which are more bluish and reddish, respectively, which could indicate an adaptation to optimize color signaling in an environment in which short and long wavelengths of light are highly filtered by the green background of mature leaves. In contrast, white forest butterflies have been found to be more dorsally yellowish than their rainforest counterparts, which could be seen as an adaptation to environments devoid of leaves and flooded by UV light.